2021
DOI: 10.31592/aeusbed.736610
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Salgını Döneminde Yenilikçi İç Davranışlarına Yeniden Bakış: Algılanan İşyeri Maneviyatının ve Psikolojik Güvenliğin Etkileri

Abstract: Recent literature has shown the contributions of positivity in organizations, but less is known about the impact of spirituality and safety feelings as an extension of positive psychology on individuals' innovative work behaviors. Considering the COVID-19 pandemic outbreak, it is suggested that the conditions encouraging employees' perceptions and attitudes as well as their innovative work behaviors (IWBs) have been changed. Based on the positive psychology approach, workplace spirituality and psychological sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…COVID-19 has established a rich breeding ground for innovative solutions and approaches, and research on innovation-related behavior is no exception (Peerzadah et al , 2022). In the pandemic context, employees’ IWB and its prerequisites have gained more importance (Taştan and İşiaçık, 2021). It demonstrates that researchers continue to be positive about the importance of innovation theory and research.…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 has established a rich breeding ground for innovative solutions and approaches, and research on innovation-related behavior is no exception (Peerzadah et al , 2022). In the pandemic context, employees’ IWB and its prerequisites have gained more importance (Taştan and İşiaçık, 2021). It demonstrates that researchers continue to be positive about the importance of innovation theory and research.…”
Section: Resultsmentioning
confidence: 99%
“…In many organizations, employees had to work at home and find new methods to work properly from home. In such tense and challenging working conditions, the workforce's innovative work behavior gained more significance Taştan, & İşiaçik, 2021[ 61 ]. Moreover, given the economic shock many firms had no option but to reduce the number of their employees.…”
Section: Introductionmentioning
confidence: 99%
“…, 2014). Comparatively, few studies identified workplace spirituality (WPS) as an essential antecedent for IWB (Hunsaker and Ding, 2022; Afsar and Rehman, 2015; Taştan and Isiacik, 2021). However, to assess WPS, many of them (Bantha and Nayak, 2021; Salem et al ., 2023; Hunsaker and Ding, 2022; Alfarajat and Emeagwali, 2021) have used the questionnaires developed by Ashmos and Duchon's (2000) and Milliman et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers and practitioners have suggested different ways to promote IWB, like a psychological contract, job autonomy (Ramamoorthy et al, 2005;Bantha and Nayak, 2021), psychological climate (Montani et al, 2014) knowledge sharing (Radaelli et al, 2014). Comparatively, few studies identified workplace spirituality (WPS) as an essential antecedent for IWB (Hunsaker and Ding, 2022;Afsar and Rehman, 2015;Tas ¸tan and Isiacik, 2021). However, to assess WPS, many of them (Bantha and Nayak, 2021;Salem et al, 2023;Hunsaker and Ding, 2022;Alfarajat and Emeagwali, 2021) have used the questionnaires developed by Ashmos and Duchon's (2000) and Milliman et al (2003).…”
mentioning
confidence: 99%